From exploitation to conservation: a historical analysis of zoos and their functions in human societies - Sampaio, Marilian Boachá; Schiel, Nicola; Souto, Antonio da Silva (Ethnobiology and Conservation, 2020)
Currently there are many interfaces that allow the relationship between humans and animals, including zoos. Throughout history, the change in zoo structure has accompanied the social and cultural changes of human society. Nevertheless, despite the remarkable progress since early zoos were organized, there is still a great need for improvements of zoos around the world. A critical look at the relationship between humans and animals that led to the establishment of zoos was the aim of this study. Zoos currently follow some precepts (entertainment, education, research and conservation), however has not been enough to bind changes in zoos that still lack in accomplishing these pillars. Such lacks create a scenario for discussions between those who believe in the potential of conservation projects developed by zoos and those who find hostile and inadequate to animal life. It can be suggested that the bedrocks were the result of how human beings have perceived animals over time, since perception interferes with the way people deal with what surrounds them. In this way, the merely utilitarian vision of prehistoric times came from the perception that people had about animals at that time. Understanding the evolution of people’s perception of animals and how this perception has influenced the configuration of zoos can tell us the directions they can take from now on. We believe that the next step is to turn our attention to the visitors, not only to meet their leisure expectations, but for them to become allies in the fight for biodiversity conservatio.